Terapi Non-Farmakologi untuk Mengatasi Nyeri Dismenore pada Remaja - Husnul Khotimah; Santi Sundary Lintang (Faletehan Health Journal, 2022)
One of the complaints during menstruation is dysmenorrhea. Non-pharmacological therapy becomes the main alternative to overcome dysmenorrhea. However, few studies discuss it. The purpose of this study was to analyze various non-pharmacological therapies (aromatherapy, warm compresses, deep breathing relaxation, music therapy, and physical exercise) to treat dysmenorrhea pain in adolescents. This study used a pre experimental pretest-posttest design. Of the 114 total population, the sample was taken by using a quota sampling technique and amounted to 65. The research data analysis used Wilcoxon signed-rank test. The results showed that the 5 non-pharmacological therapies could treat dysmenorrhea pain in adolescents with P value 0.001 for aromatherapy, P value 0.001 for warm compresses, P value 0.004 for deep breath relaxation, P value 0.001 for music therapy, and P value 0.001 for physical exercise. Adolescents can do their favorite things as a non-pharmacological therapy to divert pain due to dysmenorrhea; thus, their daily activities are not disturbed and can be more productive.